Poder de compra governamental como instrumento de política pública para o desenvolvimento das micro e pequenas empresas - Proenca Junior, Milton (2020)
Small companies have an important social and economic presence in the country, either through the generation and maintenance of jobs, or through their participation in the formation of the Gross Domestic Product. In view of these aspects, the State seeks to use instruments that can stimulate their development. For that, governmental purchasing power has been used as an instrument of public policy. In this sense, this research aims to study the purchasing power of the State as an instrument to foster the development of small companies through the implementation of the Micro and Small Business Statute. In order to comply with the proposal, an investigation was carried out in the bids through the Price Registration System carried out by the State of Paraná, looking for evidence that supports the effectiveness of the policy for the promotion of small companies in the State. As a result, the study identified that even with the implementation of the favoring rule for micro and small companies, their strengthening in public procurement has shown modest results, with Complementary Law 123/2006 not being in all groups of objects acquired by the Administration holds influence. Greater regionalization of micro and small companies was also identified, with an increasing number of these headquartered in the state of Paraná.